2000
DOI: 10.2460/ajvr.2000.61.1016
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of hepatic and renal cortical echogenicity in clinically normal cats

Abstract: Quantitative determination of hepatic and renal cortical echogenicity in cats is feasible, using histogram analysis, and may be useful for early detection of diffuse parenchymal disease and for serially evaluating disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 25 publications
2
54
0
2
Order By: Relevance
“…All previous in-vivo veterinary studies reported in the literature to objectively evaluate renal cortical echogenicity were performed in healthy animals [46]. These papers presented renal cortical echogenicity assessed by means of a tissue equivalent phantom [4] or in comparison to other organs [5, 6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All previous in-vivo veterinary studies reported in the literature to objectively evaluate renal cortical echogenicity were performed in healthy animals [46]. These papers presented renal cortical echogenicity assessed by means of a tissue equivalent phantom [4] or in comparison to other organs [5, 6].…”
Section: Discussionmentioning
confidence: 99%
“…These papers presented renal cortical echogenicity assessed by means of a tissue equivalent phantom [4] or in comparison to other organs [5, 6]. It is the authors’ opinion that both these approaches have some limitations; comparison with a tissue equivalent phantom is a complicated and time consuming procedure [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em gatos, foi realizado um estudo para determinar de maneira quantitativa a ecogenicidade do fígado e cortical renal em pacientes clinicamente normais, utilizando análise de histograma. Conclui-se que os gatos normais possuem uma maior ecogenicidade da cortical em relação fígado; e apesar deste estudo ter demonstrado que a ecogenicidade do fígado e córtex renal em gatos pode ser quantificada, porém nem a avaliação ultrassonográfica qualitativa nem a quantitativa substituem a avaliação histológica (DROST et al, 2000). Nefrite intersticial e glomerular, necrose ou nefrose tubular aguda, (causado por etilenoglicol, uvas em cães e lírio em gatos), estágio terminal da doença renal e nefrocalcinose podem causar hiperecogenicidade da cortical (WALTER et al, 1987b;WALTER et al, 1988;BARR et al, 1989;BECK;SLOCOMBE, 1991;FORREST et al, 1998;EUBIG et al, 2005 (WALTER et al, 1987b).…”
Section: Ultrassonografia Renal Modo Bunclassified
“…Deve-se lembrar que a espécie felina pode apresentar vacúolos de gordura no epitélio tubular proximal causando elevação da ecogenicidade da cortical (KONDE, 1989;YEAGER;ANDERSON, 1989;DROST, 2000 Morrow et al (1996) encontrou uma média do IR de 0,61 ± 0,06 para a espécie canina, similarmente ao que foi publicado anteriormente por Nyland et al (1993), que encontrou valor médio do IR de 0,62 ± 0,05. No entanto, é sugerido valor máximo de 0.70 tanto para gatos quanto para cães (MORROW et al, 1996), o que é também o limite utilizado em medicina humana (PLATT et al, 1990).…”
Section: Análise De Correlação Entre As Medidas De Tamanho Do Rim Esqunclassified